The effect of mating experience, age and territoriality on the male mating competition in Phytoseiulus persimilis and Neoseiulus californicus (Acari: Phytoseiidae) - Hamideh Dehghani-Tafti; Azadeh Zahedi Golpayegani; Alireza Saboori; Karol Lynn Krey (Persian Journal of Acarology)
Male competition to fertilize the eggs of females would result in conflicts between the members of one sex and evolution of secondary behavioral and morphological characters. Here, we investigated the effect of previous mating experience, territoriality and age on the male mating combat and precedence in two phytoseiid species; Phytoseiulus persimilis and Neoseiulus californicus. Our results showed that naïve P. persimilis males, which had not experienced mating before the experiment, were mostly the ones who were able to mate with the females first. In N. californicus, previous experience did not have any significant effect on the male behavior. Both naïve and experienced males were able to mate females equally. Territoriality had no significant effect on male mating competition, in either P. persimilis, or N. californicus. We suggested that phytoseiid predatory mites might differ in phenotypical mating behave-iors, so that although they actively defended their mating territory, the consequences of their variation in phenotypical mating strategies led to a non-significant territoriality. The effect of age on male competing behavior was remarkable both in P. persimilis and N. californicus. P. persimilis younger males precede the elders in mating with females while in N. californicus, the older males were the ones who mated with the females first. The effects of female re-mating opportunity, the male phenotypical behavior, and spermatophore storage on male competing behavior are discussed.